A study of perceptions, attitudes, and level of knowledge among pediatricians towards attention-deficit/hyperactivity disorder - Hirfanoğlu, Tuğba; Soysal, A Sebnem; Gücüyener, Kivilcim; Cansu, Ali; Serdaroğlu, Ayşe (The Turkish Journal of Pediatrics, 2008)
The study aimed to evaluate the level of perception, attitude, and knowledge of pediatric residents to attention-deficit/hyperactivity disorder (ADHD) by a questionnaire based on the Diagnostic and Statistical Manual of Mental Disorders (4th ed) diagnostic criteria. One hundred and fifty-six pediatric residents from university and state hospitals answered a four-step Likert type questionnaire form consisting of 43 questions regarding sociodemographic features, age, duration of residency, marital status, and general knowledge of ADHD, differential diagnosis, coexisting conditions, and management of ADHD. Of the residents, 127 (81.4%) stated that their knowledge on ADHD was deficient, and 123 (85.2%) reported that they did not know the protocol used in establishing the diagnosis. There was no statistically significant difference with respect to differential diagnosis and co-morbid conditions of ADHD between the two groups (university and state hospital) (p>0.05). 60.9% of the residents were aware of the adverse effects. We believe that pediatric resident education programs must include more intensive focus on the topics of behavioral and developmental neurology as well as common neuropsychiatric disorders, and that child psychiatry and child neurology rotations, within our current rotation systems in pediatric residency training, should be extended.